The Effect of Spiritual Needs and Resiliency on Quality of Life in Diabetics - Mostafa Abdevali (Shiraz University of Medical Sciences, 2021)
Introduction: Diabetes, as the most common chronic metabolic disease, decreases the quality of life in patients. This disease causes a crisis in the physical, psychological, and spiritual aspects, which increases the use of the spiritual resource as a coping mechanism. Resilience is one of the variables that enhance the quality of life by coordinating different aspects of human life. it is considered necessary to adapt to the disease. This study aimed to investigate the effect of spiritual needs and resilience on quality of life in diabetics. Methods: The study is a descriptive-correlational one. The participants were 165 patients with cancer diseases (female 105, male 60) from Sari city selected through convenience sampling. The data were collected using the quality-of-life scale (WHO), spiritual needs scale (Büssing), and resilience scale (Connor & Davidson). For data analysis, Stepwise regression analysis was carried out by means of SPSS 19. Results: The data were analyzed using stepwise regression analysis. According to the results, there was a significant and positive correlation between scores on the components of Spiritual Needs and spiritual well- being. Moreover, subscales of the Spiritual Needs such as "Religious needs" (p < 0.001), "Existentialistic needs" (p < 0.001) "need for Inner peace" (p < 0.001) and "Actively Giving needs" (p < 0.001) had a positive correlation with the quality of life. And among all components of Spiritual Needs, Religious needs, Existentialistic needs, and Inner Peace needs had more predictive power in quality of life. And also there was a significant correlation between scores of resiliency and quality of life while the component of resiliency (p < 0.001) had more predictive power in quality of life. Conclusion: It is concluded that components of Spiritual needs and resiliency, as two psychological constructs, can play a significant role in quality of life. Therefore, developing plans and approaches to address the patients' spiritual needs and resiliency can be beneficial since it promotes quality of life in diabetics.